Liposomes: from biophysics to the design of peptide vaccines - Frézard,F. (1999)
Liposomes (lipid-based vesicles) have been widely studied as drug delivery systems due to their relative safety, their structural versatility concerning size, composition and bilayer fluidity, and their ability to incorporate almost any molecule regardless of its structure. Liposomes are successful in inducing potent in vivo immunity to incorporated antigens and are now being employed in numerous immunization procedures. This is a brief overview of the structural, biophysical and pharmacological properties of liposomes and of the current strategies in the design of liposomes as vaccine delivery systems.